European perspectives on security research - Thoma, K. (Klaus) (Acatech diskutiert, 2011)
Europe's networked societies of today are shaped by a growing interconnection in almost all areas of life. The complexity of our infrastructures and the concurrent accessibility to means of destruction by terrorist groups and individual perpetrators call for innovative security solutions. However, such evolving innovations inevitably raise fundamental questions of concern in our societies. How do we balance the imperatives of securing our citizens and infrastructures on the one hand, and of protecting of our sacredly held civil liberties on the other The topical network Safety and Security of acatech the German Academy of Science and Engineering invited experts from the science academies of various European countries to share their perspectives on security research and the aspect of safety during a two-day workshop hosted by the Fraunhofer Institute for High-Speed Dynamics, Ernst-Mach-Institut in March 2010. This publication is a compilation of contributions made during the workshop.